Kierkegaard’s Mirrors - Stokes, P. author. aut Link
XII, 223 p.
Keywords: What is it to see the world, other people, and imagined situations as making personal moral demands of us? What is it to experience stories as speaking to us personally and directly? Kierkegaard's Mirrors explores Kierkegaard's answers to these questions, with a new phenomenological interpretation of Kierkegaardian 'interest'.